Pengaruh CAR dan LDR terhadap ROA pada Bank Umum yang Terdaftar di BEI - Sabila Nur Al-fadzar; Radia Purbayati; Rosma Pakpahan (Indonesian Journal of Economics and Management, 2021)
This study aims to analyze the effect of the Capital Adequacy Ratio (CAR) and Loan to Deposits Ratio (LDR) on the Return On Assets (ROA) of Commercial Banks listed on the IDX in 2014-2019. The population of this research is commercial banks listed on the Indonesia Stock Exchange in 2014-2019, the research sample is 38 bank companies using the purposive sampling method. The analysis used is descriptive and quantitative analysis using Eviews 9 software. The results show that simultaneously the CAR and LDR variables have a significant effect on ROA. CAR has a significant negative effect on ROA and LDR has an insignificant positive effect on ROA